2012
DOI: 10.1088/0004-637x/757/1/24
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Mass and Stellar Population Distribution in M82 With the LBT

Abstract: We present a K−band spectroscopic study of the stellar and gas kinematics, mass distribution, and stellar populations of the archetypical starburst galaxy M82. Our results are based on a single spectrum at a position angle of 67.5 • through the K−band nucleus. We used the 12 CO stellar absorption band head at 2.29 µm (CO 2.29 ) to measure the rotation curve out to nearly 4 kpc radius on both the eastern and western sides of the galaxy. Our data show that the rotation curve is flat from 1 − 4 kpc. This stands i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…In the case of CRe, our models are primarily constrained by the resolved radio observations of the starburst core and radio halo. Thus, it is useful to report the electron cooling time as a function of the critical synchrotron emission frequency for a given magnetic field strength rather than as a direct function of the CRe energy (Rybicki & Lightman 1979;Ginzburg 1989). The characteristic emission frequency is related to CRe energy and B by: The width of the band indicates the effect of increasing/decreasing the free-free clumping parameter by a factor of √ 2 compared to the default value given in Table 2.…”
Section: Analytic Estimates Of Key Propagation Timescalesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of CRe, our models are primarily constrained by the resolved radio observations of the starburst core and radio halo. Thus, it is useful to report the electron cooling time as a function of the critical synchrotron emission frequency for a given magnetic field strength rather than as a direct function of the CRe energy (Rybicki & Lightman 1979;Ginzburg 1989). The characteristic emission frequency is related to CRe energy and B by: The width of the band indicates the effect of increasing/decreasing the free-free clumping parameter by a factor of √ 2 compared to the default value given in Table 2.…”
Section: Analytic Estimates Of Key Propagation Timescalesmentioning
confidence: 99%
“…The left panel of Figure 10 shows the energy density in each component, for each model. In the right panel of Figure 10, we use the steady-state CR distribution and spectra to constrain the acceleration the CRs might impart to the gas of M82 by calculating ∇P/ρ and comparing it to the acceleration due to gravity (denoted as the black solid line) calculated by Greco et al (2012). The density profiles used are those constrained from our models.…”
Section: Gas Acceleration From Cosmic Raysmentioning
confidence: 99%
See 1 more Smart Citation
“…where R is the lengthscale of the CGM and M gal is the dynamical mass of the system, which is scaled here to that of M82 (see e.g. Strickland & Heckman 2009;Greco et al 2012). The kinetic energy loss of a clump due to ram pressure drag will lead to a decay of its orbit.…”
Section: Clump Infallmentioning
confidence: 99%
“…Both analyses find a steeply rising curve, peaking at about 25 from the galaxy center and rapidly declining in a Keplerian fashion beyond 25 , likely indicating that M 82's extended disk mass is missing, which is very peculiar and exceptional for a disk galaxy. More recently, Greco et al (2012) have presented a K-band spectroscopic study and measured the M 82 rotation curve out to about 4 ( 4 kpc) on both the eastern and western sides of the galaxy. At variance with the previous studies, it has been found that the stellar rotation velocity is flat on scales of 1−4 kpc (with only a slight decline on the eastern side) with a value of 110−120 km s −1 out to 4 kpc, thus implying an M 82 total dynamical mass of ∼10 10 M .…”
Section: Introductionmentioning
confidence: 99%